2004
DOI: 10.1016/j.otohns.2004.06.515
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Residual Disease with CT Scan after Surgery of Juvenile Nasopharyngeal Angiofibroma

Abstract: study was to elucidate the effects of VCAP on sleep and the utility of awake and sleep laryngoscopy in MSA.Methods: We recruited 14 patients with MSA presenting with snoring (4 men and 10 women; mean age, 54.6 years; disease duration, 4.2 years; International Cooperative Ataxia Rating Scale [ICARS], 46.9). After performing arterial blood gas analysis, spirometry, and polysomnography (PSG), awake and sleep laryngoscopy were performed.Results: Sleep laryngoscopy revealed that 7 patients exhibited VCAP and 7 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The use of cyanoacrylate (CA) glues for polymerization in the presence of blood was proposed in the 1970s [3]. N-butyl-2-cyanoacrylate (NBCA) (Histoacryl, Avacryl and Trufill n-BCA), often referred to as the "Glues", was introduced as an embolic agent in the 1980s and Trufill n-BCA was approved by the US Food and Drug Administration (FDA) in 2000 for use in the treatment of cerebral arteriovenous malformations [4,27,28] by replacing the carcinogenic Isobutyl-2-cyanoacrylate due to its predictable polymerization qualities, ease of surgical resection, and low toxicity [29,30]. Due to the adhesive nature of NBCA, it can mechanically occupy the intravascular lumen and stop blood flow regardless of blood coagulability [4,31,32].…”
Section: Cyanoacrylate Gluesmentioning
confidence: 99%
“…The use of cyanoacrylate (CA) glues for polymerization in the presence of blood was proposed in the 1970s [3]. N-butyl-2-cyanoacrylate (NBCA) (Histoacryl, Avacryl and Trufill n-BCA), often referred to as the "Glues", was introduced as an embolic agent in the 1980s and Trufill n-BCA was approved by the US Food and Drug Administration (FDA) in 2000 for use in the treatment of cerebral arteriovenous malformations [4,27,28] by replacing the carcinogenic Isobutyl-2-cyanoacrylate due to its predictable polymerization qualities, ease of surgical resection, and low toxicity [29,30]. Due to the adhesive nature of NBCA, it can mechanically occupy the intravascular lumen and stop blood flow regardless of blood coagulability [4,31,32].…”
Section: Cyanoacrylate Gluesmentioning
confidence: 99%
“…While the implementation of intraoperative CT scanning has been reported in human medicine [11], research in veterinary medicine has been limited. A human case report suggested that in patients with juvenile nasopharyngeal angiofibroma, contrast-enhanced CT scanning 2.8 ± 1.8 days after surgery could detect residual tumor cells even when the resection was deemed complete [12]. However, in dogs, anesthesia is required to control respiration and obtain image optimization for thorough residual mass evaluation.…”
Section: Discussionmentioning
confidence: 99%